Pembelajaran Sejarah di Era Digital: Antara tantangan dan Peluang - Sumintho (Journal of Education and Learning Sciences, 2023)
The digital era has brought enormous changes to various sectors. It has such a significant impact on human life. These changes also had an impact on the education sector. Mainly for learning history. This article tries to present the challenges and opportunities for learning history in the digital era. This article is presented using a descriptive-qualitative approach based on library research. The results of the study show that the main challenges faced by history teachers are how to integrate technology in teaching history and how to teach students to process digital information critically. In addition, some history teachers also face difficulties in accessing quality historical resources.